In his 1970 paper "Selfish and Spiteful Behaviour in an Evolutionary Model", Hamilton uses Price's equation to derive his well-known rule $rb -c >0$. My question is about one of the steps in his derivation.

Hamilton considers a population of $n$ individuals. Let $s_{ij}$ be the effect of individual $i$ on the fitness of $j$. The fitness of an individual $j$ is defined as $w_j = 1 + \sum_i s_{ij}$, $w=1/n \sum_j w_j$ is the mean fitness in the population, and $q=1/n \sum_j q_j$ is the average frequency of a certain allele. Using Price's equation, we get

$w \Delta q = Cov (q_j, \sum_i s_{ij})$.

So far so good. But Hamilton then says that this equation can be rewritten as

$w\Delta q = \sum_i 1/n \sum_j (q_j - q)s_{ij}$

Based on the definition of covariance (i.e., $Cov (X,Y) = E((X-E(X))(Y-E(Y)))$, this seems to only be the case if $E(\sum_i s_{ij}) = 1/n \sum_j \sum_i s_{ij} = 0$. But this would imply that the average fitness wouldn't change over time, which sounds odd for me. In sum, I don't understand this step in Hamilton's paper. What am I missing?


Actually the derivation is pretty straightforward. It's easier to use the fact that $Cov(X,Y) = E(XY) - E(X)E(Y)$ to derive this result. Suppose $x_{j} = \sum_{i} s_{ij}$.
\begin{align*} Cov (x_j, q_{j}) &= E (x_{j}q_{j}) - E (x_{j}) E (q_{j}) \\ &= \frac{1}{n}\sum x_{j} q_{j} - \frac{1}{n}\sum x_{j} q \\ &= \frac{1}{n} \sum x_{j} (q_{j} - q) \end{align*}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.